High-Throughput Genetic Screen for Synaptogenic Factors: Identification of LRP6 as Critical for Excitatory Synapse Development - Kamal Sharma; Se-Young Choi; Yong Zhang; Thomas J.F. Nieland; Shunyou Long; Min Li; Richard L. Huganir (Cell Reports, 2013)
Genetic screens in invertebrates have discovered many synaptogenic genes and pathways. However, similar genetic studies have not been possible in mammals. We have optimized an automated high-throughput platform that employs automated liquid handling and imaging of primary mammalian neurons. Using this platform, we have screened 3,200 shRNAs targeting 800 proteins. One of the hits identified was LRP6, a coreceptor for canonical Wnt ligands. LRP6 regulates excitatory synaptogenesis and is selectively localized to excitatory synapses. In vivo knockdown of LRP6 leads to a reduction in the number of functional synapses. Moreover, we show that the canonical Wnt ligand, Wnt8A, promotes synaptogenesis via LRP6. These results provide a proof of principle for using a high-content approach to screen for synaptogenic factors in the mammalian nervous system and identify and characterize a Wnt ligand receptor complex that is critical for the development of functional synapses in vivo.